The effects of ownership change on bank performance and risk exposure: Evidence from indonesia - Shaban, Mohamed; James, Gregory A. (Journal of Banking & Finance, 2018)
This study investigates the effects of ownership change on the performance and exposure to risk of 60 Indonesian commercial banks over the period 2005–2012. We find that state-owned banks tend to be less profitable and more exposed to risk than private and foreign banks. Domestic investors tend to select the best performers for acquisition. Domestic acquisition is generally associated with a decrease in the efficiency of the acquired banks. Non-regional foreign acquisition is associated with a reduction in risk exposure. Acquisition by regional foreign investors is associated with performance gains.